Features of ovarian steroidogenesis and endometrial hypertrophy during adjuvant therapy with tamoxifen in premenopausal patients with hormone-dependent breast cancer - A. Yu. Goryainova; A. I. Stukan; A. I. Trofimenko; A. A. Meshcheryakov (Опухоли женской репродуктивной системы, 2023)
Background. Difficulties in the prevention and treatment of endometrial pathology in hormone-positive breast cancer are associated with the lack of an unambiguous understanding of the mechanisms of the effect of tamoxifen on target tissues and the development of possible hyperestrogenism.Aim. To study the effect of ovarian steroidogenesis on the endometrium during adjuvant therapy with tamoxifen in pre-menopausal patients with hormone-dependent breast cancer.Materials and methods. All patients at inclusion in the study had intact menstrual function and received adjuvant therapy with tamoxifen. Group 1 included 42 patients without chemotherapy, group 2 included 41 patients with chemotherapy. Depending on the safety of the menstrual function, each group was divided into 2 subgroups. At the control points (3, 6 and 9 months from the start of tamoxifen therapy) patients underwent transvaginal ultrasound with measurement of endometrial thickness, and also determined the content of follicle-stimulating hormone and estradiol in peripheral blood. When menstruation persisted, blood sampling and measurement of endometrial thickness were performed on days 5-8 of the menstrual cycle.Results. In subgroups 1A and 2C, patients with preserved menstrual function showed a trend towards higher values of estradiol levels and endometrial thickness, compared with subgroups 1B and 2D of patients with amenorrhea. Against this background, the absence of statistically significant intergroup differences in the content of follicle-stimulating hormone in patients receiving tamoxifen with a preserved menstrual cycle (1A and 2C) and amenorrhea (1B and 2D) attracts attention. An intragroup analysis of follicle-stimulating hormone dynamics in patients with amenorrhea without chemotherapy in subgroup 1C shows an increase in its content by 162 %, without statistically significant changes in endometrial thickness and estradiol concentration. The statistically significant increase in endometrial thickness by 25 % and the proportion of patients with increasing endometrial wall thickness in 63.3 % in the 2D subgroup in patients receiving tamoxifen, with amenorrhea and previous chemotherapy treatment are cause for concern.Conclusion. The results of the study indicate a possible additive effect of such factors as intact menstrual function before the start of treatment for hormone-positive breast cancer, chemotherapy, and the development of amenorrhea on the progressive increase in endometrial thickness when using tamoxifen in premenopausal patients.